MYTH IN POEME MON FRERE BLANC BY LEOPOLD SEDAR SENGHOR - Imelda Malawaty Simorangkir; Yulia Sofiani Zaimar (FKIP, Universitas Banten Jaya, 2023)
found in parts of France, but also in non-French speaking areas (Francophone). French literature that developed outside of France occurred due to several factors, one of which was the colonization that occurred in the nineteenth century. This research would like to investigate myth in a poem, tittle Poème à mon frère blanc, written by Leopold Sedar Senghor. In this research, the researchers will not discuss the structure of the poem, but they are interested in the hidden meaning behind the poem. This research uses the theory of Roland Barthes to analyze the hidden meaning (myth) that the speaker wants to tell. The search for the hidden meaning (myth) is carried out, because the researchers understand, in a poem, what is written is not necessarily the true meaning. This research uses qualitative and descriptive methods with reading and understanding techniques.